2022
DOI: 10.4014/jmb.2206.06037
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Quantitative Analysis Method for Phenanthrenes in Peels of the Dioscorea Genus

Abstract: Phenanthrenes are bioactive phenolic compounds found in genus Dioscorea, in which they are distributed more in peel than in flesh. Recent studies on phenanthrenes from Dioscorea sp. peels have revealed the potential for valuable biomaterials. Herein, an analytical method using highperformance liquid chromatography (HPLC) for quantitation of bioactive phenanthrenes was developed and validated. The calibration curves were obtained using the phenanthrenes (1-3) previously isolated from Dioscorea batatas concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Yams (Dioscorea spp.) are economically valued herbs and are widely used for promoting health and folk medication as well [25]. Reported biological studies revealed that D. quinqueloba extract possesses effects on cardiovascular and inflammatory skin diseases [26,27].…”
Section: Methods Applicationmentioning
confidence: 99%
“…Yams (Dioscorea spp.) are economically valued herbs and are widely used for promoting health and folk medication as well [25]. Reported biological studies revealed that D. quinqueloba extract possesses effects on cardiovascular and inflammatory skin diseases [26,27].…”
Section: Methods Applicationmentioning
confidence: 99%
“…Phenanthrene is a group of polycyclic aromatic hydrocarbons naturally occurring in various plants. Kim et al [ 32 ] quantified the contents of three phenanthrenes 2,7-dihydroxy-4,6-dimethoxyphenanthrene, 6,7-dihydroxy-2,4-dimethoxyphenanthrene, and batatasin in the pericarp of D. batatas , D. polystachya , D. quinqueloba , and D. bulbifera . The highest content of 2,7-dihydroxy-4,6-dimethoxyphenanthrene was 173.69 μg/g in D. quinqueloba .…”
Section: Bioactive Compoundsmentioning
confidence: 99%